Effects of dietary zinc and manganese sources on retention and apparent absorption rate of zinc, manganese, copper and iron in growing goats - Deng, Z. F.; Sun, Z. H.; Tayo, G. O.; Lin, B.; Tang, S. X.; Han, X. F.; Tan, Z. L. (Cuban Journal of Agricultural Science, 2010)
The study was conducted to investigate the effects of Zn and Mn sources on using trace elements in growing goats. Four 6-month-old Liuyang Black wether goats (20.0?0.5 kg) were used in a 4?4 Latin square experiment and assigned to four dietary treatments: (1) control; (2) control+lipid-coated Met-Zn chelate and lipid-coated Lys-Mn chelate (PML); (3) control+Met-Zn chelate and Lys-Mn chelate (CML); (4) control+ZnSO4?7H2O and MnSO4?H2O (FML). The amounts of Zn and Mn added in PML, CML and FML treatments were 0.020 g and 0.029 g per 100 g concentrate (DM basis) respectively. The results showed that intakes of concentrate and maize stover, and retention and apparent absorption rate of Fe and Cu were not affected by dietary zinc and manganese sources; whole tract apparent absorption rate of Zn and Mn in FML were lower than that of PML, CML and control (P < 0.05), retention of Zn per day in PML and CML was higher than that of control (P < 0.05), and retention of Mn per day in PML, CML and FML was higher than that of control (P < 0.05). The results indicated that Met-Zn and Lys-Mn supplementation can improve apparent absorption rate of Zn and Mn in growing goats, but have no impacts on apparent absorption rate of Fe and Cu. Keywords: lysine, trace element, blood parameter